Thermally-Induced Crack Evaluation in H13 Tool Steel - Abdulhadi, Hassan Abdulrssoul; S. N., Aqida; Izwan, Ismail; M., Ishak; Mohammed, Ghusoon R. (MDPI AG, 2017)
This study reported the effect of thermal wear on cylindrical tool steel (AISI H13) under aluminum die-casting conditions. The AISIH13 steels were immersed in the molten aluminum alloy at 700 C before water-quenching at room temperature. The process involved an alternating heating and cooling of each sample for a period of 24 s. The design of the immersion test apparatus stylistically simulated aluminum alloy dies casting conditions. The testing phase was performed at 1850, 3000, and 5000 cycles. The samples were subjected to visual inspection after each phase of testing, before being examined for metallographic studies, surface crack measurement, and hardness characteristics. Furthermore, the samples were segmented and examined under optical and Scanning Electron Microscopy (SEM). The areas around the crack zones were additionally examined under Energy Dispersive X-ray Spectroscopy (EDXS). The crack’s maximum length and Vickers hardness profiles were obtained; and from the metallographic study, an increase in the number of cycles during the testing phase resulted in an increase in the surface crack formation; suggesting an increase in the thermal stress at higher cycle numbers. The crack length of Region I (spherically shaped) was about 47 to 127 m, with a high oxygen content that was analyzed within 140 m from the surface of the sample. At 700 C, there is a formation of aluminum oxides, which was in contact with the surface of the H13 sample. These stresses propagate the thermal wear crack length into the tool material of spherically shaped Region I and cylindrically shape Region II, while hardness parameters presented a different observation. The crack length of Region I was about 32% higher than the crack length of Region II.